Efektivitas Media Dart Board Modifikasi terhadap Kemampuan Kognitif dalam Mengenal Buah-buahan bagi Anak Usia Dini - Wahyuni, Tasya Tri; Ismet, Syahrul (Darul Yasin Al Sys, 2023)
The lack of growth in children's cognitive capacities to identify objects around them, such as the fact that children still struggle to recognize fruit, particularly its color, shape, and size, is what inspired this research. The research purpose is to evaluate the impact of dart board media on young children's cognitive development with regard to fruit comprehension. This study employs quasi-experimental techniques along with a quantitative approach. This study included every student at the Pembina Pasaman State Kindergarten, which had 115 students spread across six classes. Using a purposive sample technique, the sample of 17 kids from classes B6 and B1 was selected. Tests were used to collect the data, and tests for homogeneity, hypothesis testing, normality, and effect size were used to analyze the data. Therefore, the pre-test.